World Directory of Medical Schools (World Health Organization, 2000)
This 7th edition of the World Directory of Medical Schools is a country-by-country listing of 1,642 institutions of basic medical education approved by the competent national authorities in 157 countries or areas; the information reflects academic year 1995-96. The directory also provides information on the conditions for obtaining the license to practice medicine in 14 countries that do not have medical schools. Entries are alphabetical by country and by individual medical schools. Country data includes total population, number of physicians per 100,000 population, number of medical schools, duration of basic medical degree course, degree awarded, and information about medical registration/license to practice. School entries include the year instruction started; the language of instruction; duration of the basic medical degree course, including practical training; entrance examination requirements; and whether foreign students are eligible for admission. This edition also includes information on national regulations governing medical registration and the license to practice and on the existence of bilateral or multilateral agreements relating to the mutual recognition of physicians' qualifications or experience. A database similar to the printed directory is being constructed based on two questionnaires. (RH)